PERBANDINGAN EFEKTIVITAS PEMBELAJARAN BERBASIS TEKNOLOGI DAN PEMBELAJARAN KONVENSIONAL PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SDN SUKAHARJA 2 - Ihda Hayatunnisa; Hisa Fakhriya; Siti Habibah Muti'ah; Nurrachman Ramadhan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to compare the effectiveness of technology-based learning and conventional learning in the subject of Islamic Religious Education (PAI) at SDN Sukaharja 2. This study was motivated by technological developments in the field of education, which encourage teachers to utilize more engaging and interactive learning media to make the teaching and learning process more engaging and interactive. The research method used was a quantitative approach with a comparative study design. The research subjects were students at SDN Sukaharja 2 who participated in conventional learning. In technology-based learning, the teacher used PowerPoint (PPT) and digital quizzes as tools for delivering material and evaluating learning, while conventional learning was conducted through lectures and direct explanations by the teacher without the use of technological media. Data collection was conducted through observation, questionnaires, and student achievement tests. The data was analyzed using statistical techniques to determine the differences in the effectiveness of the two types of instruction. The results of the study indicate that technology-based learning is more effective than conventional learning. The use of PowerPoint presentations and digital quizzes was able to increase students’ attention and understanding of Islamic Religious Education (IRE) material. Additionally, students became more active and enthusiastic in participating in the learning process. Thus, the use of simple technological media such as PowerPoint presentations and digital quizzes can serve as an effective alternative for improving the quality of Islamic Religious Education in elementary schools.